Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-17T12:58:42-03:00
A)

S={ \frac{1}{6}, \frac{1}{3}  }

vamos aplicar na formula

 x^{2} -Sx +P=0

S= \frac{1}{6} + \frac{1}{3} = \frac{1+2}{6}= \frac{3}{6} = \frac{1}{2}

P= \frac{1}{6} . \frac{1}{3} = \frac{1}{18}

substituindo na formula

 x^{2} + \frac{x}{2} + \frac{1}{18} =0

tirando mmc=18
fica

18x² +9x +1=0


b) = c)

S={- \frac{1}{2} , \frac{1}{5} }

S=- \frac{1}{2} + \frac{1}{5} = \frac{-5+2}{10} =- \frac{3}{10}

P=- \frac{1}{2}. \frac{1}{5} =- \frac{1}{10}

substituindo na formula

 x^{2} -Sx+P=0

 x^{2} + \frac{3}{10}x- \frac{1}{10}  =0

mmc=10

fica

10x² + 3x -1 =0




1 5 1